Breastfeeding Videos as a New Training Tool for Malaysian Breastfeeding Peer Counsellor Program in Empowering Breastfeeding Communities - Md Monoto, Ezura Madiana; Mohamad Alwi, Nor Kamariah (IIUM Medical Journal Malaysia, 2018)
The Malaysian Breastfeeding Peer Counsellors (MBFPC) is the pioneer of non-governmental organization (NGO) of trained breastfeeding peer counsellors in Malaysia initiated in 2010. The training was done in a systematic way using a developed syllabus that was adapted from and endorsed by the La Leche League International (LLLI) to suit our local population. Training materials used throughout the program were presentation slides, demonstration tools, mantas and role-plays. Materials and methods: In 2015, MBFPC partnered with Global Health Media Project (GHMP) to incorporate breastfeeding videos as training tool to further enhance the delivery of current breastfeeding peer counsellor trainings to the participants, emphasizing on helping breastfeeding mothers. The new training tool was evaluated in 38 participants, who underwent 21 hours of training. Participants were required to do pre and post-assessments to complete the MBFPC Modules, view 8 videos and do practical sessions within a 2 month period post training. Participants’ field experience survey and focus group discussions were conducted among the participants and the trainers to look at the practicality of the videos in our training. Results: All participants felt that the videos made the training more effective and helped change their understanding and approach. The trainers agreed that the videos had covered all key topics need to be delivered in the training modules and helped them to deliver most important topics in helping breastfeeding mothers in a more practical way. Conclusion: GHMP Breastfeeding Videos are suitable as educational and training tools in helping breastfeeding mothers in our training.